INVESTIGATING THE NEXUS BETWEEN PERSONALITY TRAITS AND ISLAMIC WORK ETHICS - Mastura Ab. Wahab, (Asian Academy of Management Journal, 2017)
This study examines the nexus between personality traits and Islamic work ethics (IWE) among employees in Malaysia. The data were drawn from 182 participants who completed a 36-item personality traits questionnaire and the short version of the 17-item IWE questionnaire. Data were analysed using Smart PLS version 3.2. Instead of using IWE as one composite factor which was normally done in most previous studies when researching on IWE, the present study has factor analysed the IWE and the result has generated three dimensions of IWE. The three dimensions were used as IWE's factors to test the relationships with the personality traits. The findings of the study revealed that the personality traits of openness-to-experience is a positive significant predictor of effort and competition dimensions of IWE, agreeableness is a significant positive predictor of effort dimension, while emotional instability is a negative predictor of effort dimension of IWE. The practical implication is for managers to use the finding of this study when hiring employees for jobs that require high ethical effort, competitiveness, and socially responsible work practices in their organisations. Another implication of the study is for organisations to consider some adjustments in interpreting the results when measuring the personality traits of the Muslim employees using current personality traits as developed in the West because Muslims interpret personality traits differently from the non-Muslim context.